Curriculum transformations in terms of digital competence at ELTE tók’s teacher speciality training (Training and Practice : Journal of Educational Sciences, 2018)
The Faculty of Primary and Pre-School Education of Eötvös Loránd University is developing a new curriculum for the new training and outcome requirements (as later TOR) of the new students admitted the next academic year. According to this, the main profile of our Department is to examine and develop the IT skills and digital competence in the 6-12 age group in multimedia educational curricula, ICT tools and algorhythmic thinking. That is why it is important for us that our students have those kinds of digital skills that they will be able to use properly and effectively in their work at school for their students. In my presentation, I will explain the new curricula of the new TOR specialisation of elementary student-teachers and show how the application of ICT (both theoretically and practically) appears in the case of student-teachers and in their education.